Dietary inflammatory index and the risks of non-alcoholic fatty liver disease: a systematic review and meta-analysis - Zhang, Xingfen; Ruan, Jiale; He, Yujing; Xu, Anyi; Fang, Yingying; Zhang, Qiufeng; Gu, Lihu; Liu, Xingchen (Frontiers in Nutrition, 2024)
Background: Previous studies have suggested a correlation between dietary inflammatory potential and non-alcoholic fatty liver disease (NAFLD). Therefore, the study aimed to investigate the association between dietary inflammatory potential, measured by the dietary inflammation index (DII), and NAFLD. Methods: From establishing the database to June 2023, a systematic search of PubMed, Web of Science, Embase and Cochrane Library were performed to identify relevant observational studies. These studies reported a correlation between DII and NAFLD. The meta-analysis used odds ratio (OR) with 95% confidence intervals (CI) to evaluate the relationship between DII and NAFLD. Results: Eight studies were included in this meta-analysis after excluding irrelevant records. A summary of the results from the included studies showed that the risk of NAFLD was higher in those exposed to higher DII (OR=1.26, 95%CI 1.12 to 1.40, p<0.001), with a high degree of heterogeneity (I2=85.7%, p<0.001). When DII was divided into 3 tertiles from low to high for comparison, the results showed that the risk of NAFLD was higher in Tertile 2 (T2) population compared to the Tertile 1 (T1) population (OR=1.75, 95%CI 1.20 to 2.54, p<0.005). The risk of NAFLD was significantly higher in Tertile 3 (T3) compared to the T1 population (OR=3.07, 95%CI 1.63 to 5.77, p=0.001). Conclusion: The results suggest that high DII is associated with an increased risk of NAFLD, and conversely, low DII is associated with a decreased risk of NAFLD.